Pengembangan Keterampilan Mahasiswa Program Studi Teknik Sipil Fakultas Teknik dan Ilmu Komputer Universitas Islam Indragiri Dalam Persiapan Balsa Bridge Competition and Project Cost Estimate Competition Temu Wicara Nasional 2024 - Achmad Isya Alfassa; Endy Sudeska; Syafrizal Thaher (Jurnal Pelita Pengabdian Masyarakat, 2024)
Balsa Bridge Competition is a competition held to see the skills and abilities of academics, practitioners, and students in testing the durability of bridges made of balsa wood. While the Project Cost Estimate Competition is a competition held to see a project cost estimate or often referred to as a project cost prediction. a competition that is often held by the Indonesian Civil Engineering Student Communication Forum (FKMTSI). In 2024, a National Discussion Meeting was held with Riau-Kepri as the host. At the 2024 National Discussion Meeting, the Civil Engineering Study Program, Faculty of Engineering and Computer Science, Indragiri Islamic University participated in two competitions held by the Indonesian Civil Engineering Student Communication Forum (FKMTSI), namely the Balsa Bridge Competition and the Project Cost Estimate Competition, which were held at the Indragiri Institute of Technology and Business (ITB Indragiri) Rengat, Indragiri Hulu Regency, Riau Province. Students of the Civil Engineering Study Program, Faculty of Engineering and Computer Science, Indragiri Islamic University, provided supplies and received direction before taking part in the competition conducted by lecturers from the Civil Engineering Study Program, FTIK, Indragiri Islamic University. The direction and briefing aims to increase the team's enthusiasm so that they are ready to take part in the match and provide the best results for the institution